2021
DOI: 10.1101/2021.06.05.21258404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Bacterial Microbiome Profiles Associated with Colorectal Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: Objective Recent studies have shown a potential link between gut microbiome and colorectal cancer (CRC). Initially, a wide array of research into this topic was discovered from the past decade, illustrating a keen interest in the potential causal relationship between the gut microbiome and CRC. However, the cancer research community is lacking a summarised systematic review of this kind which aims to explore the evidence linking the human gut microbiome to risk of CRC. Design This systematic review was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Decreased Bacteroides have been reported in gut microbial dysbiosis, associated with increasing serum proinflammatory responses and C-reactive protein levels . While enrichment of some members of the genus Bacteroides , such as Bacteroides fragilis, has been reported by a previous study, Bacteroides thetaiotaomicron was the member enriched in the LAC group (data not shown). However, no studies have explored the relationship between the Eubacterium nodatum group and colitis or CRC.…”
Section: Discussionmentioning
confidence: 58%
“…Decreased Bacteroides have been reported in gut microbial dysbiosis, associated with increasing serum proinflammatory responses and C-reactive protein levels . While enrichment of some members of the genus Bacteroides , such as Bacteroides fragilis, has been reported by a previous study, Bacteroides thetaiotaomicron was the member enriched in the LAC group (data not shown). However, no studies have explored the relationship between the Eubacterium nodatum group and colitis or CRC.…”
Section: Discussionmentioning
confidence: 58%
“…These findings are consistent with the findings of a systematic review conducted by Russ et al, which investigated the association between the human gut microbiome and the risk of CRC. The study found that Fusobacterium and Bacteroides were the most enriched microbial species in CRC compared to HC [ 76 ]. Another systematic review found nine fecal microbiotas ( Fusobacterium , Enterococcus , Porphyromonas , Salmonella , Pseudomonas , Peptostreptococcus , Actinomyces , Bifidobacterium, and Roseburia ) to be associated with colorectal neoplasia [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal dysbiosis in CF has been linked with increased risk of CRC [14][15][16]. Historically, CF microbiome research has focused on the paediatric population which demonstrated that CF children have reduced GI microbial diversity and fewer protective shortchain fatty acid (SCFA) producing bacteria [17][18][19].…”
Section: Introductionmentioning
confidence: 99%